Linking Strategic Planning to Strategic Performance: Mediating Effects of Organizational Agility and Strategic Maneuvering in Indonesian Financial Firms - Wiliam Santoso; Christian Herdinata; Fransisca Desiana Pranatasari (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Financial companies in Indonesia are currently facing major challenges due to technological disruptions, regulatory changes, and shifts in consumer behavior that are increasingly leading to digitalization. The use of big data is one of the keys in strategic decision-making, but the success of this digital transformation is highly dependent on the company's ability to develop strategic organizational agility, strategic maneuvering, and proper strategic planning. Objective: This study aims to analyze the influence of these three strategic factors on the strategic performance of big data-based financial companies in Indonesia. Methods: The method used is quantitative research with an explanatory research approach, involving respondents consisting of managers, division heads, and strategic decision-makers from banking, fintech, and insurance companies that have implemented big data. Data were collected by questionnaires and analyzed using the Structural Equation Modeling (SEM) Partial Least Squares (PLS) method. Results: The study shows that strategic planning has an effect on strategic maneuvering and strategic organizational agility, respectively. In terms of strategic performance, it is only significantly influenced by strategic maneuvering, but not significantly by strategic organizational agility or strategic planning. Meanwhile, strategic organizational agility does not mediate the influence of strategic planning on strategic performance. Interestingly, strategic maneuvering fully mediates the relationship between strategic planning and strategic performance. Conclusion: In big data analytics (BDA)-based financial companies in Indonesia, strategic maneuvering not strategic organizational agility is the decisive mechanism through which strategic planning translates into superior strategic performance.